The physics of plasmas - Boyd, T. J. M. (Cambridge University Press, 2003)
"Advanced undergraduate and graduate students of physics, applied mathematics, astronomy and engineering will find a clear but rigorous explanation of the fundamental properties of plasmas with minimal mathematical formality. This book will also appeal to research physicists and nuclear and electrical engineers."--Jacket